2016
DOI: 10.1007/s00261-016-0913-6
|View full text |Cite
|
Sign up to set email alerts
|

Liver fibrosis staging with diffusion-weighted imaging: a systematic review and meta-analysis

Abstract: DWI is a reliable noninvasive technique with good diagnostic accuracy for LF staging. Using b ≥ 800 s/mm, high-field strength (3.0 T) and IVIM-DWI can optimize the diagnostic performance of DWI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 56 publications
4
40
0
Order By: Relevance
“…Considering pancreatic hardness is associated with fibrosis, a low ADC value due to a hard texture can be explained by the decreased diffusion of water and the high density of fibrin within the tissue. The usefulness of the ADC to evaluate for fibrosis or hardness of the tissue has already been proven in other organs such as the liver and kidney[19-21]. In our study, the minimal ADC value showed a higher degree of correlation than the mean ADC value.…”
Section: Discussionsupporting
confidence: 50%
“…Considering pancreatic hardness is associated with fibrosis, a low ADC value due to a hard texture can be explained by the decreased diffusion of water and the high density of fibrin within the tissue. The usefulness of the ADC to evaluate for fibrosis or hardness of the tissue has already been proven in other organs such as the liver and kidney[19-21]. In our study, the minimal ADC value showed a higher degree of correlation than the mean ADC value.…”
Section: Discussionsupporting
confidence: 50%
“…An example DW-EPI data set (after averaging and before normalization) is shown in Figure 4. Red arrows point to regions with undesirable signal attenuation caused by cardiac motion, which becomes apparent in the left liver lobe when α is more than 1.5 s/mm 2 (e.g., when b = [200, 300 s/mm 2 ] for α 4 and b = 300 s/mm 2 for α 3 ). Moreover, bright vessels were apparent on images acquired with α 0 when b was less than 100 s/mm 2 , as highlighted by the blue arrows.…”
Section: In Vivo Imagingmentioning
confidence: 99%
“…IVIM was first investigated in the brain, but has recently seen growing interest in more highly perfused organs such as the liver, 3,4 pancreas, 5 kidney, 6 prostate, 7 and the heart. [8][9][10] The liver has a unique vasculature system due to 2 main blood supplies, namely, the hepatic artery and the portal vein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high b value for liver fibrosis imaging (between 800 and 1000 s/mm 2 ) could significantly increase the diagnostic accuracy of diffusion imaging in differentiating between significant and severe fibroses (>F2). For diagnosing liver cirrhosis (F4), the use of 3T MRI equipment has also proved to optimize the DWI diagnostic accuracy, compared to 2T MRI [45].…”
Section: Diffusion-weighted Mr Imagingmentioning
confidence: 99%